Edukasi Dan Pendampingan Pemanfaatan Teknologi Tepat Guna Melalui Smart Filter Air Sumur Bor Kawasan Perumnas Sijambi Kota Tanjungbalai - Ruri Prihatini Lubis; Yenni Ramadhani Harahap; Riska Franita (Jurnal Masyarakat Indonesia (Jumas), 2025)
The Directorate General of Water Resources of the Ministry of Public Works and Public Housing (2014) stated that the problem of scarcity and unequal access to clean water in Indonesia is caused by increasing water demand, such as population growth, increased agricultural, industrial, mining, hotel activities, and the expansion of residential areas [1]. The clean water crisis and scarcity are also occurring in Tanjungbalai City. The President Director of PDAM Tirta Kualo invited the Director of UNESCO Asia Pacific, Prof. Shahbaz Khan, to conduct research on the crisis and poor water quality in Tanjungbalai City. One area of ​​Tanjungbalai City that is urgently affected by the scarcity and unequal access to clean water is the community of housewives in Perumnas Sijambi, Tanjungbalai City. The Perumnas Sijambi housewives social group became partners in this community service activity. These partners are customers of PDAM Tirta Kualo, whose service utilizes drilled well water as a source of clean water, although the water quality is not suitable for drinking. The main problems that are obstacles to the business of the Sijambi Housewives Group partners in Tanjung Balai City are 1) Production Aspects, because the income level of partners is still very low and the local PDAM has not fulfilled the provision of clean water to customers, resulting in the quality of water production; 2) Social Aspects of the Community, the Health Condition of the partners' drilled well water is in an unhealthy condition and is not suitable for drinking. The solution provided by the community service team to overcome the business obstacles mentioned above by designing and making a PILOT PROJECT of Appropriate Technology Tools (TTG) "SMART WELL WATER FILTER in the form of a DRILLED WELL WATER FILTER with a Green Building Concept, namely combining a Water Purification System from Natural Materials with a Paludarium that has Business Value. The tutorial on using the TTG Smart Well Water Filter Tool was carried out by the community service team to partners through several stages, namely: a) Coordination in the Preparation of Educational Socialization Activities in PKM Implementation Activities and Designing/Making the TTG Tool Pilot Project and Mentoring the TTG Smart Well Water Filter Tool Installation Workshop to Partners; b) Carrying out the activity "Mentoring the Installation Workshop for the Utilization of Appropriate Technology Smart Well Water Filter Tools in the Perumnas Sijambi Area, Tanjungbalai City"; c) Carrying out the activity "Socialization and Education on the Utilization of Appropriate Technology Through Smart Well Water Filters in the Perumnas Sijambi Area, Tanjungbalai City"; Sijambi Region, Tanjungbalai City"; d) Carrying out the Inauguration of the Smart Water Filter Appropriate Technology Tool for Borehole Wells, which was Inaugurated by the Head of Perumnas Sijambi with Partners and Local Community Members; e) Carrying out the activity of "Workshop and Education and Mentoring of Business Strategy for Housewives of Perumnas Sijambi in Marketing the Smart Water Filter Appropriate Technology Tool for Borehole Wells"; f) Carrying out the activity of "Workshop and Education and Mentoring Tutorial on Using the Smart Water Filter Tool for Borehole Wells to Get Healthy Water According to Permenkes No. 23 of 2023". The impact of the TTG Smart Water Filter Tool for partners is estimated to increase in: 1) Increasing the level of partner empowerment: Production Aspect (Increased Income) as evidenced by the increase in the quality of the partner's well water production to be healthy and drinkable will create business opportunities to increase the partner's household income by 5% with the existence of this appropriate technology tool that can be marketed/sold to the wider community; 2) Increasing the level of partner empowerment: Social Aspects (Health Improvement) as proven by the TTG Smart Well Water Filter Tool being able to improve the health quality of partner's well water. Based on laboratory tests after using the Smart Well Water Filter, iron levels returned to normal and the water was odorless and no longer brownish in color, in accordance with the standards of PERMENKES No. 2 of 2023 concerning drinking water quality requirements, namely with a Ph of 6.8.